On the application of Human Reliability Analysis in healthcare: Opportunities and challenges. (February 2020) - Sujan, Mark A.; Embrey, David; Huang, Huayi
Highlights: Experience-based analysis of opportunities and challenges for using HRA in health. Considers reliability, performance variability, regulator, and patient role. HRA should have clinical engagement and patient participation. HRA cost-effectiveness should be rigorously evaluated. HRA can provide requisite imagination and build social safety infrastructure. Abstract: Safety in healthcare is a relatively recent field, but has received considerable attention over the past 15 years. Healthcare organisations have been encouraged to learn from safety management practices in other industries. In this paper we analyse opportunities and challenges for the application of Human Reliability Analysis (HRA) in healthcare. We consider the poor levels of reliability of many healthcare processes, performance variability, the absence of regulatory frameworks that incentivise proactive risk management, and the unique role of the patient. We conclude that HRA could provide a useful framework for the analysis and reduction of risk in healthcare, but techniques might have to be adapted and applied with due consideration of the specifics of the cultural and regulatory context of this domain. This includes clinical engagement with and ownership of the HRA process, greater focus on rigorous evaluation of cost-effectiveness of HRA techniques, and active involvement of patients.